Implementing Photovoice in Teaching Speaking to the Tenth Grade Students of SMA (SLUA) Saraswati 1 Denpasar - Widiadnya, I Gusti Ngurah Bagus Yoga (International Journal for Educational and Vocational Studies, 2019)
This classroom action study dealt with implementing photovoice in teaching speaking to the tenth grade students of SMA (SLUA) Saraswati 1 Denpasar. The purpose of study the student could explain about a picture that showed in the slide show orally. The study have been stated as the following: speaking skill at the tenth grade students of SMA (SLUA) Saraswati 1 Denpasar can be improved through photovoice. This study was conducted in X IPA class that consisted of 36 females and 13 males. These subjects were chosen because faced by the fact that the subjects under study still low in speaking English and lack of confident. It was proved that the mean score of pre-test was 59.18. To enhance the improvement of their speaking skill, the researcher tried to apply photovoice technique. The researcher conducted Cycle I and the results of the data analysis of the reflection were 70.81. Then, the researcher continued the research by conducting the cycle II and the result of the data analysis of reflections in cycle II were 81.02. The finding showed that there was improvement of the students scores after the implementing of photovoice technique. In addition, the results of the questionnaire showed that option A was 72.47%, option B was 20.70%, option C was 6.81%, and option D was 0%. From the result of the study, it could be concluded that photovoice technique could improve speaking skill of the tenth grade students of SMA (SLUA) Saraswati 1 Denpasar.